(3eMGVQGJ aj JaSjQ GdbQBf GdcQjes - (3GdgGTej, eMeO LeGds ((3HNW GdeDdas)
(3ChdgG (B:s
(3Gddge eGdc Gdedc JDJj Gdedc ef JTGA(B... (3hJQRb ef JTGA HZjQ MSGH(B... (3ceG jbhd GdQGRj LhGHGs
(3BNQgG (B:s
(3YjSi GHf eQje Yed dg CLQg YfO QHg(B... (3dCf Gddg dG jMH GdXGdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs